Either Art Or Advertising? Arguments To Defend The Artistic Nature Of Advertising - Murcia Serrano, Inmaculada (Estudios de Filosofía, 2011)
This article attempts to show that the arguments to deny the artistic nature of creative advertising usually rest on false foundations, which plays down its truth. Neither the argument of the formula, nor that of the passivity of the viewer, or the futility of art, such as Noël Carroll has characterized, are valid for this purpose. Furthermore we lack of a definitive and universal concept of “artwork”, so it is impossible to deny the artistic nature of advertising.